IMPLEMENTASI PEMASARAN DIGITAL DALAM MENINGKATKAN PENDAPATAN PELAKU UMKM DESA PANTAI MEKAR - Erlianalistiani Erlianalistiani; Rafika Rahmawati; Ria Marginingsih (Universitas Islam 45 Bekasi, 2023)
Digital marketing implemented by MSMEs in Pantai Mekar Village is based on market segmentation, target market, and positioning for the lower middle class, upper middle class because the prices given are cheaper than the general market price. The obstacles that occur in MSMEs are the lack of promotion in marketing their products, the lack of effective and efficient promotion and not carrying out digital promotions. The purpose of implementing this community service is to assist business actors in providing Digital-Based Online Marketing Training to Increase Online Business Sales for MSMEs in Pantai Mekar Village, Muara Gembong District, Bekasi Regency. The method of community service activities begins with the stages of preparation and field surveys. The implementation of community service is divided into three activities, namely digital marketing training for MSMEs, training on how to create digital content through workshops and practices, and evaluation of the training that has been carried out. The result of community service related to digital marketing is to become a forum and means of education and add insight to MSMEs regarding the use and utilization of digital marketing.